TEMPERATURE CHARACTERISTICS OF PHOTOBIONTS ISOLATED FROM ALPINE LICHENS (ABSTRACT) (16th Symposium on Polar Biology) - イイダ, タカアキ; ナカノ, タケト; IHDA, Taka-aki; NAKANO, Taketo (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper